Predictions of bank financing in SMEs in Mexico - Jiménez Rico, Artemio (2022)
Various empirical studies show that the lack of financing affects the economic growth of companies and that SMEs are the most affected by this restriction. Through a non-experimental and longitudinal research design of trends through the collection of data from the quarterly survey for the conjunctural evaluation of the credit market from 2010 to 2021, this study aims to determine the predictions of bank financing in SMEs from 2022 to 2024 using the Holt-Winters method. Among the results, it was found that there is a large gap in access to bank financing between SMEs and large companies. SMEs with bank debt as of December 2021 was 35.3%, while in large companies it was 56.1%. Likewise, SMEs that used new loans was 8.1%, while in large companies it was 23.6%. Predictions for 2024 indicate that there will be no significant variations. Among the main limitations to access bank financing are the capitalization of the company, the general economic situation of the country and the high interest rates.